An empirical analysis of tax revenue and FDI influence on GDP in Southeast Asian Countries - Gomes, Florentinho (Journal of Applied Sciences in Accounting, Finance, and Tax, 2025)
This study examines the effect of tax revenue and FDI on Gross Domestic Product of nations in Southeast Asia covering 2009- 2023. The objective is to determine whether higher tax collection and increased FDI inflows significantly influence GDP performance in the region. Southeast Asia, with its dynamic economic transitions and growing global integration, provides a relevant context for assessing the roles of fiscal capacity and external capital in supporting economic development. The study uses a quantitative method based on secondary panel data gathered through the World Bank, IMF e-Library, CEIC and YCharts platforms.  The examination was conducted in STATA 17, using common, fixed, and random effects models for assessing how the variables are related. Results indicate a strong link between tax revenue and GDP, significant at the 1% threshold. FDI also demonstrates a significant positive effect, at the 5% level. These results show that improving how countries collect taxes and making it easier for foreign investors to invest can help boost overall GDP performance. The study also provides governments clear guidance on how better tax policies and investment strategies can strengthen their economies.